Improving performance in juvenile ski jumping: optimization of ski angles in the flight phase - Petrat, J.; Bessone, V. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to analyse and optimize ski angles in the flight phase of juvenile ski jumpers focusing on flying technique and equipment. Inertial measurement units (IMU) installed on jumper´s skis and 2d motion analysis were used to display kinematics in the flight phase. Results show deficits in flying technique and individual´s adjustment of the binding system. Guidelines for coaches and athletes could be derived and implemented